Molding resin composition and electronic component device

By using the resin composition for forming silicon dioxide, alumina and calcium titanate particles in the sealing material of semiconductor components, the problem of high tangent of dielectric loss in high-frequency communication is solved, and the equilibrium of dielectric constant and signal is achieved Improved efficiency supports miniaturization of substrates and packaging.

CN119173586APending Publication Date: 2024-12-20RESONAC CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380032312.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-31
Filing Date
2023-03-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In high-frequency communication, the sealing materials of conventional semiconductor components have reduced signal transmission efficiency due to high dielectric loss tangent, and it is difficult to suppress excessive increase or decrease in the dielectric constant at the same time, affecting the miniaturization of substrates and semiconductor packages.

Method used

Using a resin composition for forming a molding containing silica particles, alumina particles and calcium titanate particles, a hardened substance with low dielectric loss tangent is prepared by optimizing the proportion of inorganic filler and the selection of hardeners for use in the Sealing of electronic parts.

Benefits of technology

It realizes the reduction of dielectric loss tangent while maintaining an appropriate dielectric constant, improves signal transmission efficiency, and supports miniaturization of substrate and semiconductor packages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069409810000071
    Figure BDA0005069409810000071
  • Figure BDA0005069409810000081
    Figure BDA0005069409810000081
  • Figure BDA0005069409810000091
    Figure BDA0005069409810000091
Patent Text Reader

Abstract

A resin composition for molding, comprising a curable resin and an inorganic filler, the inorganic filler comprising silica particles and / or alumina particles and calcium titanate particles, the content of the calcium titanate particles being 10 vol% or more and less than 30 vol% with respect to the total amount of the inorganic filler, and the content of the calcium titanate particles being 10 vol% or more and less than 30 vol% with respect to the total amount of the inorganic filler. The total content of the inorganic filler is more than 60 vol% with respect to the total amount of the molding resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a molding resin composition and an electronic component device. Background Art

[0002] With the recent demand for electronic devices to be more functional, thin and small, the high-density integration and mounting of electronic parts have been continuously promoted, and the semiconductor packages used in these electronic devices have increased more than ever before, and miniaturization has been promoted. Furthermore, the high frequency of radio waves used for communication in electronic devices is also being promoted.

[0003] From the perspective of miniaturization of semiconductor packages and coping with high frequencies, high dielectric constant resin compositions for sealing semiconductor elements have been proposed (for example, see Japanese Patent Publication No. 2015-036410, Japanese Patent Publication No. 2017-057268, and Japanese Patent Publication No. 2018-141052). Summary of the invention

[0004] [Problems to be solved by the invention]

[0005] As the material of the electronic parts such as the sealing semiconductor element, for example, the molding resin composition comprising curable resin and inorganic filler can be cited. As the molding resin composition, if the material with high dielectric loss tangent is used, the transmission signal is converted into heat due to the transmission loss, and the communication efficiency is easily reduced. Here, the amount of transmission loss generated by the electric wave sent for communication and heat conversion in the dielectric body is expressed as the product of the square root of the frequency, the relative dielectric constant and the dielectric loss tangent. That is, the transmission signal is easily converted into heat in proportion to the frequency. Moreover, in recent years, in order to cope with the increase of the number of channels accompanying the diversified information, the electric wave used in the communication is high-frequencyized, so it is required to form a molding resin composition of a hardened material with low relative dielectric constant and low dielectric loss tangent. On the other hand, the larger the relative dielectric constant, the more miniaturization of the substrate, the miniaturization of the semiconductor package, etc. can be realized, so from the perspective of the suppression of transmission loss and the miniaturization of the substrate, it is desirable to suppress the excessive rise and decline of the relative dielectric constant, and ensure the low dielectric loss tangent while maintaining the relative dielectric constant.

[0006] An object of the present disclosure is to provide a molding resin composition capable of molding a cured product having a low dielectric loss tangent while maintaining a relative dielectric constant, and an electronic component device using the same.

[0007] [Technical means to solve the problem]

[0008] Specific means for solving the above-mentioned problems include the following aspects.

[0009] <1> A molding resin composition comprising:

[0010] hardening resin; and

[0011] The inorganic filler comprises at least one of silica particles and alumina particles and calcium titanate particles.

[0012] The content of the calcium titanate particles is 10 volume % or more and less than 30 volume % relative to the total amount of the inorganic filler.

[0013] The total content of the inorganic filler exceeds 60% by volume based on the total amount of the molding resin composition.

[0014] <2> The molding resin composition according to <1>, wherein the curable resin includes an epoxy resin, and the molding resin composition further includes a curing agent.

[0015] <3> The molding resin composition according to <2>, wherein the curing agent contains an active ester compound.

[0016] <4> The molding resin composition according to <3>, wherein the curing agent further includes a phenol curing agent.

[0017] <5> The molding resin composition according to any one of <2> to <4>, wherein the epoxy resin includes at least one of an o-cresol novolac-type epoxy resin, a biphenyl aralkyl-type epoxy resin, and a biphenyl-type epoxy resin.

[0018] <6> The molding resin composition according to any one of <1> to <5>, wherein the inorganic filler contains alumina particles.

[0019] <7> The molding resin composition according to any one of <1> to <6>, further comprising a stress relaxation agent.

[0020] <8> The molding resin composition according to <7>, wherein the stress relaxation agent comprises at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide.

[0021] <9> The molding resin composition according to any one of <1> to <8>, wherein the content of the silicone-based stress relaxation agent is 5% by mass or less based on the total amount of the molding resin composition.

[0022] <10> The molding resin composition according to <8>, which does not contain a silicone-based stress relaxant.

[0023] <11> The molding resin composition according to any one of <1> to <10>, which does not contain titanium compound particles other than calcium titanate particles.

[0024] <12> The molding resin composition according to any one of <1> to <11>, which is used for a high-frequency device.

[0025] <13> The molding resin composition according to <12>, which is used for sealing electronic components in high-frequency devices.

[0026] <14> The molding resin composition according to any one of <1> to <13>, which is used for encapsulating an antenna.

[0027] <15> An electronic component device, comprising:

[0028] Supporting members;

[0029] an electronic component, arranged on the supporting member; and

[0030] A cured product of the molding resin composition according to any one of <1> to <14> for sealing the electronic component.

[0031] <16> The electronic component device according to <15>, wherein the electronic component includes an antenna.

[0032] [Effects of the Invention]

[0033] According to the present disclosure, there are provided a molding resin composition capable of molding a cured product having a low dielectric loss tangent while maintaining a relative dielectric constant, and an electronic component device using the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] none DETAILED DESCRIPTION

[0035] In the present disclosure, the term "process" includes processes that are independent of other processes and processes that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved.

[0036] In the present disclosure, in a numerical range represented by “to”, numerical values ​​described before and after including “to” are respectively regarded as the minimum value and the maximum value.

[0037] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range may also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range may also be replaced by the value shown in the embodiment.

[0038] In the present disclosure, each component may include a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, unless otherwise specified, the content or content of each component refers to the total content or content of the plurality of substances present in the composition.

[0039] In the present disclosure, multiple types of particles corresponding to each component may be included. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component refers to the value for the mixture of the multiple types of particles present in the composition unless otherwise specified.

[0040] In the present disclosure, the “total content of silica particles and alumina particles” may be replaced by “the content of silica particles” or may be replaced by “the content of alumina particles”.

[0041] In the present disclosure, “the total of silica particles and alumina particles” may be replaced by “silica particles” or may be replaced by “alumina particles”.

[0042] Hereinafter, the method for implementing the present disclosure is described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, its constituent elements (including element steps, etc.) are not necessarily required except for the cases specifically indicated. The same is true for numerical values ​​and their ranges, and the present disclosure is not limited.

[0043] <Molding resin composition>

[0044] The molding resin composition of the present embodiment includes a curable resin and an inorganic filler, wherein the inorganic filler includes at least one of silica particles and alumina particles and calcium titanate particles, wherein the content of the calcium titanate particles is 10% by volume or more and less than 30% by volume relative to the total amount of the inorganic filler, and the total content of the inorganic filler exceeds 60% by volume relative to the total amount of the molding resin composition.

[0045] As described above, with respect to the molding resin composition, it is required to suppress transmission loss in the hardened material after molding. With respect to the viewpoint of suppressing transmission loss, it is ideal to realize low dielectric loss tangent, and with respect to the viewpoints of suppression of transmission loss and miniaturization of substrate, miniaturization of semiconductor package, etc., it is preferred to suppress the excessive rise and fall of relative dielectric constant and obtain the balance of relative dielectric constant. In the molding resin composition of the present embodiment, by combining at least one of silica particles and alumina particles with calcium titanate particles, making the content of calcium titanate particles relative to the total amount of inorganic filler 10 volume % or more and less than 30 volume %, and making the total content of inorganic filler relative to the total amount of molding resin composition exceed 60 volume %, it is possible to shape a hardened material with low dielectric loss tangent while maintaining a relative dielectric constant suitable for suppression of transmission loss and miniaturization of substrate, miniaturization of semiconductor package, etc.

[0046] Furthermore, the molding resin composition of the present embodiment can be molded into a cured product having a lower dielectric loss tangent by using calcium titanate particles, compared with the case of using barium titanate or the like.

[0047] Hereinafter, each component constituting the molding resin composition will be described. The molding resin composition of the present embodiment contains a curable resin and an inorganic filler, and may contain other components as necessary.

[0048] (hardening resin)

[0049] The molding resin composition in the present embodiment contains a curable resin.

[0050] The curable resin may be any of a thermosetting resin and a photocurable resin, but is preferably a thermosetting resin from the viewpoint of mass productivity.

[0051] Examples of the thermosetting resin include epoxy resins, phenol resins, melamine resins, urea resins, unsaturated polyester resins, alkyd resins, urethane resins, polyimide resins such as bismaleimide resins, polyamide resins, polyamideimide resins, silicone resins, acrylic resins, etc. From the viewpoint of formability and electrical properties, the thermosetting resin is preferably at least one selected from the group consisting of epoxy resins and polyimide resins, more preferably at least one selected from the group consisting of epoxy resins and bismaleimide resins, and even more preferably epoxy resins.

[0052] The molding resin composition may contain only one type of curable resin, or may contain two or more types of curable resins.

[0053] Hereinafter, epoxy resin will be described as an example of curable resin.

[0054] -Epoxy resin-

[0055] The molding resin composition preferably contains an epoxy resin as a curable resin.

[0056] When the molding resin composition contains epoxy resin as the curable resin, the total content of the epoxy resin relative to the curable resin is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more. The total content of the epoxy resin relative to the curable resin may be 100% by mass.

[0057] The type of the epoxy resin is not particularly limited as long as it has an epoxy group in the molecule.

[0058] Specific examples of epoxy resins include: novolac-type epoxy resins (phenol novolac-type epoxy resins, o-cresol novolac-type epoxy resins, etc.) obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aliphatic aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde under an acidic catalyst to obtain a novolac resin, and then epoxidizing the novolac resin; and triphenylmethane-type phenol resins obtained by condensing or co-condensing the phenolic compound with an aromatic aldehyde compound such as benzaldehyde and salicylaldehyde under an acidic catalyst, and then epoxidizing the triphenylmethane-type phenol resins. triphenylmethane epoxy resin obtained by epoxidizing a phenol resin; a copolymerized epoxy resin obtained by epoxidizing a novolac resin obtained by co-condensing the phenol compound and the naphthol compound with an aldehyde compound under an acidic catalyst; a diphenylmethane epoxy resin as a diglycidyl ether of bisphenol A, bisphenol F, etc.; a biphenyl epoxy resin as a diglycidyl ether of an alkyl-substituted or unsubstituted biphenol; a distyrene epoxy resin as a diglycidyl ether of a distyrene phenol compound; an epoxy resin containing sulfur atoms as a diglycidyl ether of bisphenol S, etc.; an epoxy resin as a glycidyl ether of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; an epoxy resin as a diglycidyl ether of phthalic acid, isophthalic acid, Glycidyl ester epoxy resins of glycidyl esters of polycarboxylic acid compounds such as formic acid and tetrahydrophthalic acid; glycidylamine epoxy resins obtained by replacing the active hydrogen bonded to the nitrogen atom of aniline, diaminodiphenylmethane, isocyanuric acid, etc. with a glycidyl group; dicyclopentadiene epoxy resins obtained by epoxidizing a co-condensation resin of dicyclopentadiene and a phenol compound; alicyclic epoxy resins such as diepoxy vinylcyclohexene, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane obtained by epoxidizing an olefin bond in the molecule; glycidyl ethers as p-xylene-modified phenol resins p-xylene modified epoxy resin; meta-xylene modified epoxy resin as glycidyl ether of meta-xylene modified phenol resin; terpene modified epoxy resin as glycidyl ether of terpene modified phenol resin; dicyclopentadiene modified epoxy resin as glycidyl ether of dicyclopentadiene modified phenol resin; cyclopentadiene modified epoxy resin as glycidyl ether of cyclopentadiene modified phenol resin; polycyclic aromatic ring modified epoxy resin as glycidyl ether of polycyclic aromatic ring modified phenol resin; naphthalene type epoxy resin as glycidyl ether of phenol resin containing naphthalene ring; halogenated phenol novolac type epoxy resin; hydroquinone type epoxy resin; trimethylolpropane type epoxy resin; linear aliphatic epoxy resin obtained by oxidizing olefin bonds using peracids such as peracetic acid;Aralkyl epoxy resins obtained by epoxidizing aralkyl phenol resins such as phenol aralkyl resins and naphthol aralkyl resins. Furthermore, epoxides of acrylic resins and the like can also be cited as epoxy resins. These epoxy resins can be used alone or in combination of two or more. ;

[0059] The epoxy resin preferably includes at least any one of an o-cresol novolac epoxy resin, a biphenyl aralkyl epoxy resin, and a biphenyl epoxy resin, and more preferably includes an o-cresol novolac epoxy resin and a biphenyl epoxy resin, or a biphenyl aralkyl epoxy resin and a biphenyl epoxy resin.

[0060] The epoxy equivalent (molecular weight / number of epoxy groups) of the epoxy resin is not particularly limited. From the viewpoint of balancing various properties such as moldability, reflow resistance, and electrical reliability, the epoxy equivalent of the epoxy resin is preferably 100 g / eq to 1000 g / eq, and more preferably 150 g / eq to 500 g / eq.

[0061] The epoxy equivalent of the epoxy resin is defined as a value measured by a method in accordance with Japanese Industrial Standards (JIS) K 7236:2009.

[0062] When the epoxy resin is solid, the softening point or melting point of the epoxy resin is not particularly limited. From the viewpoint of moldability and reflow resistance, the softening point or melting point of the epoxy resin is preferably 40°C to 180°C, and from the viewpoint of operability during preparation of the molding resin composition, it is more preferably 50°C to 130°C.

[0063] The melting point or softening point of the epoxy resin is defined as a value measured by differential scanning calorimetry (DSC) or a method (ring and ball method) in accordance with JIS K 7234: 1986.

[0064] When the molding resin composition contains an epoxy resin as a curable resin, the mass ratio of the epoxy resin in the entire molding resin composition is preferably 0.5 mass % to 30 mass %, more preferably 2 mass % to 20 mass %, and further preferably 3.5 mass % to 13 mass %, from the viewpoints of strength, fluidity, heat resistance, moldability, etc.

[0065] - Hardener -

[0066] When the molding resin composition includes an epoxy resin as a curable resin, the molding resin composition may further include a curing agent. The molding resin composition preferably includes a curable resin including an epoxy resin, a curing agent, and an inorganic filler including at least one of silica particles and alumina particles and calcium titanate particles. The type of the curing agent is not particularly limited.

[0067] The hardener preferably contains an active ester compound. The active ester compound may be used alone or in combination of two or more. Here, the active ester compound refers to a compound having one or more ester groups that react with an epoxy group in one molecule and having a hardening effect on the epoxy resin. Furthermore, when the hardener contains an active ester compound, the hardener may contain a hardener other than the active ester compound, or may not contain a hardener other than the active ester compound.

[0068] When an active ester compound is used as a curing agent, the dielectric loss tangent of the cured product can be suppressed to be lower than when a phenol curing agent or an amine curing agent is used as a curing agent. The reason for this is presumably as follows.

[0069] In the reaction between epoxy resin and phenol hardener or amine hardener, secondary hydroxyl groups are generated. In contrast, in the reaction between epoxy resin and active ester compound, ester groups are generated instead of secondary hydroxyl groups. Since ester groups have lower polarity than secondary hydroxyl groups, the molding resin composition containing active ester compound as a hardener can suppress the dielectric loss tangent of the hardened material to be lower than the molding resin composition containing only a hardener that generates secondary hydroxyl groups as a hardener.

[0070] In addition, the polar groups in the cured product increase the water absorption of the cured product. By using an active ester compound as a curing agent, the concentration of polar groups in the cured product can be suppressed, and the water absorption of the cured product can be suppressed. Furthermore, by suppressing the water absorption of the cured product, that is, suppressing the content of H2O as a polar molecule, the dielectric loss tangent of the cured product can be suppressed to a lower level.

[0071] The type of active ester compound is not particularly limited as long as it has one or more ester groups that react with epoxy groups in the molecule. Examples of active ester compounds include phenol ester compounds, thiophenol ester compounds, N-hydroxyamine ester compounds, and esters of heterocyclic hydroxy compounds.

[0072] Examples of the active ester compound include ester compounds obtained from at least one of an aliphatic carboxylic acid and an aromatic carboxylic acid and at least one of an aliphatic hydroxyl compound and an aromatic hydroxyl compound. An ester compound using an aliphatic compound as a polycondensation component tends to have excellent compatibility with epoxy resins due to the presence of an aliphatic chain. An ester compound using an aromatic compound as a polycondensation component tends to have excellent heat resistance due to the presence of an aromatic ring.

[0073] As specific examples of active ester compounds, aromatic esters obtained by condensation reaction of aromatic carboxylic acids and phenolic hydroxyl groups can be cited. Among them, aromatic carboxylic acid components obtained by replacing 2 to 4 hydrogen atoms of aromatic rings such as benzene, naphthalene, biphenyl, diphenylpropane, diphenylmethane, diphenyl ether, diphenylsulfonic acid with carboxyl groups, monohydric phenols obtained by replacing 1 hydrogen atom of the aromatic ring with hydroxyl groups, and mixtures of polyhydric phenols obtained by replacing 2 to 4 hydrogen atoms of the aromatic ring with hydroxyl groups as raw materials are preferably used. Aromatic esters obtained by condensation reaction of aromatic carboxylic acids and phenolic hydroxyl groups. That is, aromatic esters having structural units derived from the aromatic carboxylic acid components, structural units derived from the monohydric phenols, and structural units derived from the polyhydric phenols are preferably used.

[0074] Specific examples of active ester compounds include phenol resins having a molecular structure in which a phenol compound is linked via an aliphatic cyclic hydrocarbon group, as described in Japanese Patent Laid-Open No. 2012-246367, and active ester resins having a structure obtained by reacting an aromatic dicarboxylic acid or a halide thereof with an aromatic monohydroxy compound. The active ester resin is preferably a compound represented by the following structural formula (1).

[0075] [Chemistry 1]

[0076]

[0077] In the structural formula (1), R 1 is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a phenyl group; X is an unsubstituted benzene ring, an unsubstituted naphthalene ring, a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms, or a biphenyl group; Y is a benzene ring, a naphthalene ring, or a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms; k is 0 or 1; and n represents the average number of repetitions and is 0 to 5.

[0078] Specific examples of the compound represented by the structural formula (1) include the following exemplary compounds (1-1) to (1-10): t-Bu in the structural formula is a tert-butyl group.

[0079] [Chemistry 2]

[0080]

[0081] [Chemistry 3]

[0082]

[0083] Other specific examples of the active ester compound include a compound represented by the following structural formula (2) and a compound represented by the following structural formula (3) described in JP-A-2014-114352.

[0084] [Chemistry 4]

[0085]

[0086] In the structural formula (2), R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms, Z is an ester-forming structural site (z1) or a hydrogen atom (z2) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, and at least one of Z is an ester-forming structural site (z1).

[0087] In the structural formula (3), R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms, Z is an ester-forming structural site (z1) or a hydrogen atom (z2) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, and at least one of Z is an ester-forming structural site (z1).

[0088] Specific examples of the compound represented by the structural formula (2) include the following exemplary compounds (2-1) to (2-6).

[0089] [Chemistry 5]

[0090]

[0091] Specific examples of the compound represented by the structural formula (3) include the following exemplary compounds (3-1) to (3-6).

[0092] [Chemistry 6]

[0093]

[0094] As the active ester compound, commercially available products can also be used. As commercially available products of the active ester compound, active ester compounds containing a dicyclopentadiene-type diphenol structure include "EXB9451", "EXB9460", "EXB9460S", and "HPC-8000-65T" (manufactured by DIC Co., Ltd.); active ester compounds containing an aromatic structure include "EXB9416-70BK", "EXB-8", and "EXB-9425" (manufactured by DIC Co., Ltd.); active ester compounds containing acetylated products of phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Co., Ltd.); active ester compounds containing benzoylated products of phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Co., Ltd.), etc.

[0095] The ester equivalent (molecular weight / number of ester groups) of the active ester compound is not particularly limited, but is preferably 150 g / eq to 400 g / eq, more preferably 170 g / eq to 300 g / eq, and even more preferably 200 g / eq to 250 g / eq from the viewpoint of balancing various properties such as formability, reflow resistance, and electrical reliability.

[0096] The ester equivalent of the active ester compound is set to a value measured by a method in accordance with JIS K 0070:1992.

[0097] From the viewpoint of suppressing the dielectric loss tangent of the cured product to be low, the equivalent ratio (ester group / epoxy group) of the epoxy resin to the active ester compound is preferably 0.9 or more, more preferably 0.95 or more, and still more preferably 0.97 or more.

[0098] From the viewpoint of reducing the amount of unreacted components of the active ester compound, the equivalent ratio (ester group / epoxy group) of the epoxy resin to the active ester compound is preferably 1.1 or less, more preferably 1.05 or less, and still more preferably 1.03 or less.

[0099] The hardener may also contain other hardeners other than the active ester compound. The type of other hardener is not particularly limited and can be selected according to the desired properties of the molding resin composition. Examples of other hardeners include phenol hardeners, amine hardeners, acid anhydride hardeners, polythiol hardeners, polyaminoamide hardeners, isocyanate hardeners, blocked isocyanate hardeners, and the like.

[0100] Specific examples of the phenol curing agent include: polyphenol compounds such as resorcinol, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenols; novolac-type phenol resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenol compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, phenylphenol, aminophenol, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde in the presence of an acid catalyst; and polyphenol compounds such as polyphenols obtained by condensing or co-condensing the phenolic compounds with dimethoxy-p-xylene, bis(methoxymethyl)biphenyl, and the like. Synthetic aralkyl phenol resins such as phenol aralkyl resins and naphthol aralkyl resins; p-xylene-modified phenol resins and m-xylene-modified phenol resins; melamine-modified phenol resins; terpene-modified phenol resins; dicyclopentadiene-type phenol resins and dicyclopentadiene-type naphthol resins synthesized by copolymerizing the above-mentioned phenolic compounds with dicyclopentadiene; cyclopentadiene-modified phenol resins; polycyclic aromatic ring-modified phenol resins; biphenyl-type phenol resins; triphenylmethane-type phenol resins obtained by condensing or co-condensing the above-mentioned phenolic compounds with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acidic catalyst; phenol resins obtained by copolymerizing two or more of these, etc. These phenolic hardeners may be used alone or in combination of two or more.

[0101] The functional group equivalent weight (hydroxyl group equivalent weight in the case of phenolic hardener) of the other hardener is not particularly limited. From the viewpoint of balancing various properties such as formability, reflow resistance, and electrical reliability, the functional group equivalent weight of the other hardener is preferably 70 g / eq to 1000 g / eq, and more preferably 80 g / eq to 500 g / eq.

[0102] The functional group equivalent of other curing agents (hydroxyl group equivalent in the case of a phenol curing agent) is set to a value measured by a method in accordance with JISK 0070:1992.

[0103] The softening point or melting point of the curing agent is not particularly limited. From the viewpoint of moldability and reflow resistance, the softening point or melting point of the curing agent is preferably 40°C to 180°C, and from the viewpoint of workability during production of the molding resin composition, more preferably 50°C to 130°C.

[0104] The melting point or softening point of the curing agent is set to a value measured in the same manner as the melting point or softening point of the epoxy resin.

[0105] The equivalent ratio of epoxy resin to hardener (all hardeners when multiple hardeners are used), i.e., the ratio of the number of functional groups in the hardener to the number of functional groups in the epoxy resin (number of functional groups in the hardener / number of functional groups in the epoxy resin) is not particularly limited. From the perspective of suppressing the respective unreacted components to a small extent, it is preferably set in the range of 0.5 to 2.0, and more preferably in the range of 0.6 to 1.3. From the perspective of formability and reflow resistance, it is further preferably set in the range of 0.8 to 1.2.

[0106] The curing agent may include at least one other curing agent selected from the group consisting of a phenol curing agent, an amine curing agent, an acid anhydride curing agent, a polythiol curing agent, a polyaminoamide curing agent, an isocyanate curing agent, and a blocked isocyanate curing agent, and an active ester compound. From the viewpoint of providing excellent bending toughness of the molding resin composition after curing, the curing agent may include a phenol curing agent and an active ester compound, may include an aralkyl phenol resin and an active ester compound, may include an aralkyl phenol resin, a melamine-modified phenol resin, and an active ester resin.

[0107] Hereinafter, other hardeners may also be referred to as phenol hardeners.

[0108] When the hardener contains an active ester compound and other hardeners, from the viewpoint of suppressing the dielectric loss tangent of the hardened material to a low level, the mass ratio of the active ester compound in the total amount of the active ester compound and other hardeners is preferably 40 mass % or more, more preferably 60 mass %, further preferably 80 mass % or more, particularly preferably 85 mass % or more, and particularly preferably 90 mass % or more.

[0109] When the hardener contains an active ester compound and other hardeners, from the viewpoint of suppressing the dielectric loss tangent of the hardened material to be low, the total mass ratio of the epoxy resin and the active ester compound in the total amount of the epoxy resin and the hardener is preferably 40 mass % or more, more preferably 60 mass %, further preferably 80 mass % or more, particularly preferably 85 mass % or more, and particularly preferably 90 mass % or more.

[0110] When the curing agent contains an active ester compound and other curing agents, the mass ratio of the active ester compound in the total amount of the active ester compound and other curing agents is preferably 40 mass % to 90 mass %, more preferably 50 mass % to 80 mass %, and further preferably 55 mass % to 70 mass %, from the viewpoint of excellent flexural toughness of the molding resin composition after curing and from the viewpoint of suppressing the dielectric loss tangent of the cured product to a low level.

[0111] When the curing agent includes an active ester compound and other curing agents, the mass ratio of the other curing agent in the total amount of the active ester compound and other curing agents is preferably 10 mass % to 60 mass %, more preferably 20 mass % to 50 mass %, and further preferably 30 mass % to 45 mass %, from the viewpoint of excellent flexural toughness of the molding resin composition after curing and from the viewpoint of suppressing the dielectric loss tangent of the cured product to a low level.

[0112] When the molding resin composition contains an epoxy resin and a curing agent, the content of the curable resin other than the epoxy resin may be less than 5 mass %, 4 mass % or less, or 3 mass % or less relative to the total amount of the molding resin composition.

[0113] -Polyimide resin-

[0114] The molding resin composition may contain a polyimide resin as a curable resin.

[0115] The polyimide resin is not particularly limited as long as it is a polymer compound having an imide bond. Examples of the polyimide resin include bismaleimide resins.

[0116] As the bismaleimide resin, copolymers of compounds having two or more N-substituted maleimide groups and compounds having two or more amino groups can be cited. Hereinafter, compounds having two or more N-substituted maleimide groups are also referred to as "polymaleimide compounds", and compounds having two or more amino groups are also referred to as "polyamino compounds".

[0117] Bismaleimide resin can be a polymer obtained by polymerizing a composition comprising a polymaleimide compound and a polyamino compound, or can include units derived from other compounds other than the polymaleimide compound and the polyamino compound. As other compounds, compounds having a base comprising two or more ethylenic unsaturated double bonds can be listed. Hereinafter, compounds having a base comprising two or more ethylenic unsaturated double bonds are also referred to as "ethylenic compounds".

[0118] The polymaleimide compound is not limited as long as it is a compound having two or more N-substituted maleimide groups, and may be a compound having two N-substituted maleimide groups or a compound having three or more N-substituted maleimide groups. From the viewpoint of easy availability, the polymaleimide compound is preferably a compound having two N-substituted maleimide groups.

[0119] Specific examples of the polymaleimide compound include bis(4-maleimidephenyl)methane, bis(3-maleimidephenyl)methane, polyphenylmethane maleimide, bis(4-maleimidephenyl)ether, bis(4-maleimidephenyl)sulfone, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, imide, meta-phenylene bismaleimide, para-phenylene bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, 1,2-bismaleimide ethane, 1,6-bismaleimide hexane, 1,12-bismaleimide dodecane, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, 1,6-bismaleimide-(2,4,4-trimethyl)hexane, etc.

[0120] These polymaleimide compounds may be used alone or in combination of two or more.

[0121] The polyamino compound is not limited as long as it is a compound having two or more amino groups, and may be a compound having two amino groups or a compound having three or more amino groups. From the viewpoint of easy availability, the polyamino compound is preferably a compound having two amino groups.

[0122] Specific examples of the polyamino compound include 4,4'-diaminodiphenylmethane, 4,4'-diamino-3,3'-dimethyl-diphenylmethane, 4,4'-diamino-3,3'-diethyl-diphenylmethane, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl ketone, 4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis[4-(4-aminophenyl)propane] 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 1,3-bis[1-(4-(4-aminophenoxy)phenyl)-1-methylethyl]benzene, 1,4-bis[1-(4-(4-aminophenoxy)phenyl)-1-methylethyl]benzene, 4,4'-[1,3-phenylenebis(1-methylethylidene)]dianiline, 4,4'-[1,4-phenylenebis(1-methylethylidene)]dianiline, 3,3'-[1,3-phenylenebis(1-methylethylidene)]dianiline, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 9,9-bis(4-aminophenyl)fluorene, and the like.

[0123] These polyamino compounds may be used alone or in combination of two or more.

[0124] Examples of the "group containing an ethylenically unsaturated double bond" possessed by the ethylenic compound include vinyl, allyl, vinyloxy, allyloxy, acryloyl, methacryloyl, etc. The ethylenic compound may have only one type of group containing an ethylenically unsaturated double bond in one molecule, or may have two or more types.

[0125] The ethylenic compound may have other groups in addition to the group containing an ethylenically unsaturated double bond. Examples of the other groups include an amino group, an ether group, and a thioether group.

[0126] Specific examples of the vinyl compound include diallylamine, diallyl ether, diallyl sulfide, triallyl isocyanurate, and the like.

[0127] The equivalent ratio (Ta1 / Ta2) of the number of N-substituted maleimide groups (Ta1) of the polymaleimide compound to the number of amino groups (Ta2) of the polyamino compound in the bismaleimide resin is preferably in the range of 1.0 to 10.0, more preferably in the range of 2.0 to 10.0.

[0128] In addition, when the bismaleimide resin contains units derived from ethylenic compounds, the equivalent ratio (Ta3 / Ta1) of the number of ethylenic unsaturated double bonds (Ta3) of the ethylenic compound in the bismaleimide resin to the number of N-substituted maleimide groups (Ta1) of the polymaleimide compound can be, for example, in the range of 0.05 to 0.2.

[0129] The weight average molecular weight of the bismaleimide resin is not particularly limited, and may be, for example, in the range of 800 to 1500, in the range of 800 to 1300, or in the range of 800 to 1100.

[0130] The weight average molecular weight of the bismaleimide resin can be determined by using gel permeation chromatography (GPC) and converting it based on a calibration curve using standard polystyrene.

[0131] The calibration curve was approximated by a cubic equation using standard polystyrene: TSK standard polystyrene (Type: A-2500, A-5000, F-1, F-2, F-4, F-10, F-20, F-40) [manufactured by Tosoh Corporation].

[0132] As the apparatus used for GPC, there are pump: L-6200 model (manufactured by Hitachi High-technologies Co., Ltd.), detector: L-3300 model RI (manufactured by Hitachi High-technologies Co., Ltd.), column oven: L-655A-52 (manufactured by Hitachi High-technologies Co., Ltd.), guard column: TSK Guardcolumn HHR-L (manufactured by Tosoh Corporation, column size 6.0 mm×40 mm), column: TSK gel-G4000HHR+gel-G2000HHR (manufactured by Tosoh Corporation, column size 7.8 mm×300 mm)

[0133] The measurement conditions of GPC include: eluent: tetrahydrofuran, sample concentration: 30 mg / 5 mL, injection volume: 20 μL, flow rate: 1.00 mL / min, and measurement temperature: 40°C.

[0134] When the molding resin composition contains a polyimide resin as a curable resin, the mass ratio of the polyimide resin in the entire molding resin composition is, for example, 0.5 mass % to 30 mass %, preferably 2 mass % to 20 mass %, and more preferably 3.5 mass % to 13 mass %.

[0135] (hardening accelerator)

[0136] The molding resin composition in this embodiment may contain a curing accelerator as needed. The type of the curing accelerator is not particularly limited, and can be selected according to the type of curable resin, the required properties of the molding resin composition, and the like.

[0137] Examples of the curing accelerator used in the molding resin composition containing at least one selected from the group consisting of epoxy resins and polyimide resins as a curable resin include diazabicycloolefins such as 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) and 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 2-heptadecanediol, 2-heptadecyl imidazole ... Cyclic amidine compounds such as imidazole; derivatives of the cyclic amidine compounds; phenol novolac salts of the cyclic amidine compounds or their derivatives; compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone and other quinone compounds, compounds with π bonds such as diazonophenylmethane and the like to these compounds; tetraphenylborate of DBU, tetraphenylborate of DBN, tetraphenylborate of 2-ethyl-4-methylimidazole, tetraphenylborate of N-methylmorpholine cyclic amidinium compounds such as salts; tertiary amine compounds such as pyridine, triethylamine, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; derivatives of the tertiary amine compounds; ammonium salt compounds such as tetra-n-butylammonium acetate, tetra-n-butylammonium phosphate, tetraethylammonium acetate, tetra-n-hexylammonium benzoate, and tetrapropylammonium hydroxide; primary phosphines such as ethylphosphine and phenylphosphine, secondary phosphines such as dimethylphosphine and diphenylphosphine, triphenylphosphine, diphenyl(p-toluene)phosphine, tri(alkylphenyl)phosphine, tri(alkoxyphenyl)phosphine, tri(alkyl·alkoxyphenyl)phosphine, tri(dialkylphenyl)phosphine, tri(trialkylphenyl)phosphine, tri(tetraalkylphenyl)phosphine, tri(dialkoxyphenyl)phosphine )phosphine, tri(trialkoxyphenyl)phosphine, tri(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, alkyldiarylphosphine, trinaphthylphosphine, tri(benzyl)phosphine and other tertiary phosphine; phosphine compounds such as complexes of the above-mentioned organic phosphine and organic boron; compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone, anthraquinone and other quinone compounds, diazonophenylmethane and other compounds having π bonds to the above-mentioned organic phosphine or the above-mentioned phosphine compound;The organic phosphine or the phosphine compound is reacted with 4-bromophenol, 3-bromophenol, 2-bromophenol, 4-chlorophenol, 3-chlorophenol, 2-chlorophenol, 4-iodophenol, 3-iodophenol, 2-iodophenol, 4-bromo-2-methylphenol, 4-bromo-3-methylphenol, 4-bromo-2,6-dimethylphenol, 4-bromo-3,5-dimethylphenol, 4-bromo-2,6-di-tert-butylphenol, 4-chloro-1-naphthol, 1-bromo-2-naphthol, 6- Compounds with intramolecular polarization obtained by reacting halogenated phenol compounds such as bromo-2-naphthol and 4-bromo-4'-hydroxybiphenyl and then undergoing a dehydrohalogenation process; tetraphenyl phosphonium and other tetrasubstituted phosphoniums, tetraphenyl phosphonium tetra-p-toluene borate and other tetraphenyl borate salts of tetrasubstituted phosphoniums; tetrasubstituted phosphonium compounds such as salts of tetrasubstituted phosphonium and phenol compounds; salts of tetraalkyl phosphonium and partial hydrolyzates of aromatic carboxylic anhydrides; phosphate betaine compounds; adducts of phosphonium compounds and silane compounds, etc. ;

[0138] The hardening accelerator may be used alone or in combination of two or more.

[0139] Among these, the curing accelerator is preferably a curing accelerator containing an organic phosphine. Examples of the curing accelerator containing an organic phosphine include phosphine compounds such as the organic phosphine and complexes of the organic phosphine and organic boron, and compounds having intramolecular polarization formed by adding a compound having a π bond to the organic phosphine or the phosphine compound.

[0140] Among these, particularly preferred curing accelerators include triphenylphosphine, an adduct of triphenylphosphine and a quinone compound, an adduct of tributylphosphine and a quinone compound, and an adduct of tri-p-tolylphosphine and a quinone compound.

[0141] When the molding resin composition contains a hardening accelerator, the amount of the hardening accelerator is preferably 0.1 to 30 parts by mass, more preferably 1 to 15 parts by mass, relative to 100 parts by mass of the resin component. If the amount of the hardening accelerator is 0.1 parts by mass or more relative to 100 parts by mass of the resin component, there is a tendency to cure well in a short time. If the amount of the hardening accelerator is 30 parts by mass or less relative to 100 parts by mass of the resin component, there is a tendency to obtain a good molded product whose hardening speed is not too fast.

[0142] Here, the resin component refers to a curable resin and a curing agent used as needed. In addition, 100 parts by mass of the resin component means that the total amount of the curable resin and the curing agent used as needed is 100 parts by mass.

[0143] (hardening initiator)

[0144] When the molding resin composition contains a polyimide resin as a curable resin, the molding resin composition may contain a curing initiator as necessary.

[0145] Examples of the curing initiator include radical polymerization initiators that generate free radicals by heat, etc. Specific examples of the curing initiator include inorganic peroxides, organic peroxides, and azo compounds.

[0146] Examples of the inorganic peroxide include potassium persulfate (dipotassium persulfate), sodium persulfate, and ammonium persulfate.

[0147] Examples of the organic peroxide include ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide, peroxyketals such as 1,1-di(tert-butylperoxy)cyclohexane and 2,2-di(4,4-di(tert-butylperoxy)cyclohexyl)propane, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, hydroperoxides such as tert-butyl hydroperoxide, α,α'-di(tert-butylperoxy)diisopropylbenzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, Dialkyl peroxides such as tert-butylcumyl peroxide, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, di-tert-butyl peroxide, diacyl peroxides such as dibenzoyl peroxide and di(4-methylbenzoyl) peroxide, peroxydicarbonates such as di-n-propyl peroxydicarbonate and diisopropyl peroxydicarbonate, peroxyesters such as 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-hexyl peroxybenzoate, tert-butyl peroxybenzoate, and tert-butyl peroxy-2-ethylhexanoate, etc.

[0148] Examples of the azo compound include azobisisobutyronitrile, azobis-4-methoxy-2,4-dimethylvaleronitrile, azobiscyclohexanone-1-carbonitrile, and azobisbenzoyl.

[0149] When the molding resin composition contains a curing initiator, the content of the curing initiator can be 0.1 to 8.0 parts by mass relative to 100 parts by mass of the polyimide compound, and is more preferably 0.5 to 6.0 parts by mass from the viewpoint of curability. If the content of the curing initiator is 8.0 parts by mass or less, there is a tendency that volatile components are not easily generated, and the generation of voids during curing is further suppressed. In addition, by setting the content of the curing initiator to 1 part by mass or more, there is a tendency that the curability becomes better.

[0150] (Inorganic filler)

[0151] The molding resin composition in the present embodiment contains an inorganic filler including calcium titanate particles and at least one of silica particles and alumina particles.

[0152] The inorganic filler may include other fillers besides silica particles, alumina particles, or calcium titanate particles.

[0153] -At least one of silica particles and alumina particles-

[0154] The inorganic filler includes at least one of silica particles and alumina particles. The inorganic filler may include only one of silica particles and alumina particles, or may include both.

[0155] The silica particles and the alumina particles may be used alone or in combination of two or more. The silica particles and the alumina particles may be a mixture of two or more fillers having different volume average particle sizes.

[0156] The silica particles are not particularly limited, and examples thereof include fused silica, crystalline silica, and glass. The shape of the silica particles is not particularly limited, and examples thereof include spherical, elliptical, and irregular shapes. The silica particles may be crushed particles.

[0157] The silica particles may be surface-treated particles.

[0158] The shape of the alumina particles is not particularly limited, and examples thereof include spherical, elliptical, and irregular shapes. The alumina particles may be crushed particles.

[0159] The aluminum oxide particles may be surface-treated particles.

[0160] From the viewpoint of dielectric constant and thermal conductivity, the inorganic filler preferably contains alumina particles.

[0161] The total content of the silica particles and the alumina particles is preferably more than 70% by volume and not more than 95% by volume, more preferably 75% by volume to 90% by volume, and still more preferably 75% by volume to 85% by volume, based on the total amount of the inorganic filler.

[0162] The content rate (volume %) of silica particles, the content rate (volume %) of alumina particles, and the content rate (volume %) of calcium titanate particles relative to the total amount of the inorganic filler can be determined by the following method.

[0163] A thin slice sample of a cured product of a molding resin composition is photographed using a scanning electron microscope (SEM). An arbitrary area S is determined in the SEM image, and the total area A of the inorganic filler contained in the area S is obtained. Next, the elements of the inorganic filler are determined using SEM-EDX (scanning electron microscopy-energydispersive X-ray spectrometer), thereby obtaining the total area B of specific particles such as silica particles, alumina particles, and calcium titanate particles contained in the total area A of the inorganic filler. The value obtained by dividing the total area B of the specific particles by the total area A of the inorganic filler is converted into a percentage (%), and the value is set as the content (volume %) of the specific particles relative to the total amount of the inorganic filler.

[0164] The area S is set to be sufficiently large relative to the size of the inorganic filler. For example, it is set to be large enough to contain 100 or more inorganic fillers. The area S may also be the total of a plurality of cut surfaces.

[0165] When the inorganic filler includes silica particles and alumina particles, the volume ratio of alumina particles to silica particles, i.e., alumina particles:silica particles, may be 10:90 to 90:10, 30:70 to 90:10, 50:50 to 90:10, or 70:30 to 90:10.

[0166] From the viewpoint of low dielectric loss tangent, the total content of silica particles and alumina particles is preferably 30 to 85 volume %, more preferably 35 to 80 volume %, and further preferably 40 to 75 volume % based on the total amount of the molding resin composition.

[0167] In the molding resin composition, from the viewpoint of the balance between dielectric loss tangent and fluidity, the mass ratio of the total amount of silica particles and alumina particles to the total amount of epoxy resin and hardener (the total amount of silica particles and alumina particles / the total amount of epoxy resin and hardener) is preferably 1 to 25, more preferably 2 to 20, further preferably 3 to 15, and particularly preferably 4 to 12.

[0168] The volume average particle size of the silica particles and the volume average particle size of the alumina particles are not particularly limited. The volume average particle size of the silica particles and the volume average particle size of the alumina particles are each independently preferably 0.2 μm to 100 μm, more preferably 0.5 μm to 50 μm. When the volume average particle size is 0.2 μm or more, the viscosity increase of the molding resin composition tends to be further suppressed. When the volume average particle size is 100 μm or less, the filling property of the molding resin composition tends to be further improved.

[0169] Regarding the volume average particle size of the silica particles and the volume average particle size of the alumina particles, the molding resin composition is placed in a crucible and placed at 800° C. for 4 hours to be ashed. The obtained ash can be observed by SEM, separated by shape and the particle size distribution can be obtained based on the observed image, and the volume average particle size of the silica particles and the volume average particle size of the alumina particles as the volume average particle size (D50) can be obtained from the particle size distribution. In addition, the volume average particle size of the silica particles and the volume average particle size of the alumina particles can also be obtained by measurement using a laser diffraction / scattering particle size distribution measuring device (e.g., LA920, manufactured by Horiba, Ltd.).

[0170] Regarding the volume average particle size of the silica particles and the volume average particle size of the alumina particles, from the perspective of the viscosity of the molding resin composition, they can each independently be greater than 3 μm, or greater than 5 μm, and from the perspective of the fluidity of the molding resin composition, they can each independently be greater than 10 μm, or greater than 20 μm.

[0171] -Calcium titanate particles-

[0172] The shape of the calcium titanate particles is not particularly limited, and examples thereof include spherical, elliptical, and irregular shapes. The calcium titanate particles may also be crushed calcium titanate particles.

[0173] The calcium titanate particles may be surface-treated calcium titanate particles.

[0174] The calcium titanate particles may be a mixture of two or more fillers having different volume average particle sizes.

[0175] The volume average particle size of the calcium titanate particles is preferably 0.1 μm to 100 μm, more preferably 0.2 μm to 80 μm, further preferably 0.5 μm to 30 μm, particularly preferably 0.5 μm to 10 μm, and most preferably 0.5 μm to 8 μm.

[0176] The volume average particle size of calcium titanate particles can be measured as follows. The molding resin composition is placed in a crucible and placed at 800°C for 4 hours to ashed. The ash obtained can be observed by SEM, separated by shape and the particle size distribution can be obtained based on the observed image, and the volume average particle size of the calcium titanate particles as the volume average particle size (D50) can be obtained from the particle size distribution. In addition, the volume average particle size of the calcium titanate particles can also be obtained by measuring by a laser diffraction / scattering particle size distribution measuring device (e.g., HORIBA, Ltd., LA920).

[0177] From the viewpoint of the balance between dielectric constant and dielectric loss tangent, the content of calcium titanate particles is 10% by volume or more and less than 30% by volume, preferably 15% to 25% by volume, and more preferably 20% to 25% by volume, relative to the total amount of the inorganic filler.

[0178] From the viewpoint of the balance between dielectric constant and dielectric loss tangent, the content of calcium titanate particles is preferably 5 to 30% by volume, more preferably 7 to 25% by volume, and still more preferably 10 to 20% by volume based on the total amount of the molding resin composition.

[0179] In the molding resin composition, from the viewpoint of the balance between dielectric loss tangent and fluidity, the mass ratio of calcium titanate particles to the total of epoxy resin and hardener (calcium titanate particles / total of epoxy resin and hardener) is preferably 1 to 10, more preferably 1.2 to 8, further preferably 1.5 to 6, and particularly preferably 2 to 5.

[0180] -Other filling materials-

[0181] The inorganic filler may include other fillers besides silica particles, alumina particles, or calcium titanate particles.

[0182] The shape of the other filler is not particularly limited, and examples thereof include spherical, elliptical, and irregular shapes. In addition, the other filler may be a crushed filler.

[0183] Other fillers may also be surface-treated fillers.

[0184] The other filler may be used alone or in combination of two or more. The other filler may be a mixture of two or more fillers having different volume average particle sizes.

[0185] The types of other fillers are not particularly limited. Specific examples of other fillers include inorganic materials such as calcium carbonate, zirconium silicate, calcium silicate, silicon nitride, aluminum nitride, boron nitride, beryllium oxide, zircon, zircon, forsterite, steatite, spinel, mullite, titanium dioxide, talc, clay, and mica.

[0186] As other fillers, inorganic fillers having a flame retardant effect may also be used. Examples of inorganic fillers having a flame retardant effect include aluminum hydroxide, magnesium hydroxide, composite metal hydroxides such as composite hydroxides of magnesium and zinc, and zinc borate.

[0187] Other fillers may include titanium compound particles other than calcium titanate particles. Examples of titanium compound particles other than calcium titanate particles include strontium titanate particles, barium titanate particles, potassium titanate particles, magnesium titanate particles, lead titanate particles, aluminum titanate particles, lithium titanate, and titanium oxide particles.

[0188] Among them, from the viewpoint of suppressing the dielectric loss tangent of the cured product to be low, the content of the barium titanate particles is preferably less than 1 volume %, more preferably less than 0.5 volume %, and further preferably less than 0.1 volume % relative to the total amount of the inorganic filler. That is, the inorganic filler preferably does not contain the barium titanate particles, or contains the barium titanate particles at the above content.

[0189] In addition, the total content of titanium compound particles other than calcium titanate particles may be less than 1 volume%, less than 0.5 volume%, or less than 0.1 volume% relative to the total amount of the inorganic filler. That is, the inorganic filler may not contain titanium compound particles other than calcium titanate particles, or may contain titanium compound particles other than calcium titanate particles in the above content.

[0190] The preferred ranges of the volume average particle diameter of other fillers are the same as the preferred ranges of the volume average particle diameter of the silica particles and the volume average particle diameter of the alumina particles.

[0191] -Total content and characteristics of inorganic fillers-

[0192] From the viewpoint of controlling the fluidity and strength of the cured product of the molding resin composition, the total content of the inorganic filler contained in the molding resin composition is more than 60 volume % relative to the total amount of the molding resin composition, and is preferably more than 60 volume % and not more than 90 volume %, more preferably 62 volume % to 85 volume %, further preferably 65 volume % to 85 volume %, particularly preferably 68 volume % to 80 volume %, and extremely preferably 70 volume % to 78 volume %.

[0193] The content (volume %) of the inorganic filler in the molding resin composition can be determined by the following method.

[0194] A thin slice sample of a cured product of the molding resin composition is photographed using a scanning electron microscope (SEM). An arbitrary area S is determined in the SEM image, and the total area A of the inorganic filler contained in the area S is obtained. The value obtained by dividing the total area A of the inorganic filler by the area S is converted into a percentage (%), and the value is set as the content (volume %) of the inorganic filler in the molding resin composition.

[0195] The area S is set to be sufficiently large relative to the size of the inorganic filler. For example, it is set to be large enough to contain 100 or more inorganic fillers. The area S may also be the total of a plurality of cut surfaces.

[0196] Inorganic fillers may have a ratio deviation in the gravity direction when the molding resin composition is cured. In such a case, when photographing with SEM, the entire hardened material in the gravity direction is photographed, and the area S including the entire hardened material in the gravity direction is determined.

[0197] The relative dielectric constant of the inorganic filler as a whole at 10 GHz may be, for example, in the range of not more than 80. Hereinafter, the relative dielectric constant at 10 GHz may also be simply referred to as “dielectric constant”.

[0198] As a method for making the dielectric constant of the inorganic filler as a whole 80 or less, for example, there is a method of using uncalcined calcium titanate particles as calcium titanate particles. Here, uncalcined calcium titanate particles refer to calcium titanate particles that have not been exposed to a temperature of 1000° C. or higher after synthesis.

[0199] The dielectric constant of calcium titanate particles is greatly increased by calcining at a temperature of 1000° C. or higher. For example, the dielectric constant of uncalcined calcium titanate calcined at 1000° C. for 2 hours is 10 times or more the dielectric constant of calcium titanate before calcination.

[0200] From the viewpoint of suppressing dielectric loss, the dielectric constant of the inorganic filler as a whole is preferably 50 or less, more preferably 40 or less, and further preferably 30 or less. From the viewpoint of miniaturization of electronic parts such as antennas, the dielectric constant of the inorganic filler as a whole is preferably 5 or more, more preferably 10 or more, and further preferably 15 or more. From the viewpoint of suppressing dielectric loss and miniaturization of electronic parts such as antennas, the dielectric constant of the inorganic filler as a whole is preferably 5 to 50, more preferably 10 to 40, and further preferably 15 to 30.

[0201] Here, the dielectric constant of the entire inorganic filler is obtained, for example, as follows.

[0202] Specifically, three or more measuring resin compositions containing an inorganic filler and a specific curable resin of the measuring object and having different contents of the inorganic filler are prepared, and a measuring resin composition containing the specific curable resin and not containing an inorganic filler is prepared. As a measuring resin composition containing an inorganic filler and a specific curable resin of the measuring object, for example, there can be listed: a measuring resin composition containing a biphenyl aralkyl type epoxy resin, a phenol curing agent as a phenol aralkyl type phenol resin, a curing accelerator containing an organic phosphine, and an inorganic filler of the measuring object. In addition, as three or more measuring resin compositions with different contents of inorganic fillers, for example, there can be listed a measuring resin composition in which the total content of the inorganic filler relative to the measuring resin composition is 10 volume %, 20 volume %, and 30 volume %.

[0203] The prepared resin compositions for measurement were formed by compression molding under the conditions of a mold temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 600 seconds to obtain a cured product for measurement. The relative dielectric constant of each cured product for measurement obtained at 10 GHz was measured, and a graph was prepared with the content of the inorganic filler as the horizontal axis and the measured value of the relative dielectric constant as the vertical axis. Based on the obtained graph, a linear approximation was performed by the least squares method, and the relative dielectric constant when the content of the inorganic filler was 100% by volume was obtained by extrapolation, and it was used as the "dielectric constant of the entire inorganic filler".

[0204] [Various additives]

[0205] The molding resin composition in the present embodiment may contain various additives such as coupling agents, ion exchangers, mold release agents, flame retardants, colorants, and stress relaxants in addition to the above-mentioned components. The molding resin composition in the present embodiment may contain various additives known in the technical field as needed in addition to the additives exemplified below.

[0206] (Coupling agent)

[0207] The molding resin composition in the present embodiment may include a coupling agent. From the viewpoint of improving the adhesion between the resin component and the inorganic filler, the molding resin composition preferably includes a coupling agent. As the coupling agent, known coupling agents such as epoxy silane, mercapto silane, amino silane, alkyl silane, ureide silane, vinyl silane, disilazane and the like, titanium compounds, aluminum chelate compounds, aluminum / zirconium compounds and the like can be cited.

[0208] When the molding resin composition contains a coupling agent, the amount of the coupling agent is preferably 0.05 to 5 parts by mass, more preferably 0.1 to 2.5 parts by mass, relative to 100 parts by mass of the inorganic filler. If the amount of the coupling agent is 0.05 parts by mass or more relative to 100 parts by mass of the inorganic filler, there is a tendency for the adhesion with the frame to be further improved. If the amount of the coupling agent is 5 parts by mass or less relative to 100 parts by mass of the inorganic filler, there is a tendency for the moldability of the package to be further improved.

[0209] (Ion Exchanger)

[0210] The molding resin composition in the present embodiment may also contain an ion exchanger. From the viewpoint of improving the moisture resistance and high temperature placement characteristics of the electronic component device including the sealed electronic component, the molding resin composition preferably contains an ion exchanger. There is no particular limitation on the ion exchanger, and existing known ion exchangers can be used. Specifically, hydrotalcite compounds and hydroxides containing at least one element selected from the group consisting of magnesium, aluminum, titanium, zirconium and bismuth can be listed. The ion exchanger can be used alone or in combination of two or more. Among them, the hydrotalcite represented by the following general formula (A) is preferred.

[0211] Mg (1-X) Al X (OH)2(CO3) X / 2 ·mH2O……(A)

[0212] (0<X≦0.5, m is a positive number)

[0213] When the molding resin composition contains an ion exchanger, the content of the ion exchanger is not particularly limited as long as it is a sufficient amount to capture ions such as halogen ions. For example, the content of the ion exchanger is preferably 0.1 to 30 parts by mass, and more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the resin component.

[0214] (Release Agent)

[0215] From the viewpoint of obtaining good demoulding properties from the mold during molding, the molding resin composition of the present embodiment may also include a mold release agent. The mold release agent is not particularly limited, and a known mold release agent can be used. Specifically, ester waxes such as palm wax, montanic acid, stearic acid, higher fatty acids, higher fatty acid metal salts, montanic acid esters, oxidized polyethylene, non-oxidized polyethylene, and other polyolefin waxes can be listed. The mold release agent can be used alone or in combination of two or more.

[0216] When the molding resin composition includes a release agent, the amount of the release agent is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the resin component. If the amount of the release agent is 0.01 parts by mass or more relative to 100 parts by mass of the resin component, there is a tendency to fully obtain releasability. If it is 10 parts by mass or less, there is a tendency to obtain better adhesion.

[0217] (Flame Retardant)

[0218] The molding resin composition of the present embodiment may also contain a flame retardant. The flame retardant is not particularly limited, and existing known flame retardants can be used. Specifically, organic compounds or inorganic compounds containing halogen atoms, antimony atoms, nitrogen atoms or phosphorus atoms, metal hydroxides, etc. can be cited. The flame retardant can be used alone or in combination of two or more.

[0219] When the molding resin composition contains a flame retardant, the amount of the flame retardant is not particularly limited as long as it is a sufficient amount to obtain the desired flame retardant effect. For example, the amount of the flame retardant is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the resin component.

[0220] (Colorant)

[0221] The molding resin composition of the present embodiment may also include a colorant. As a colorant, known colorants such as carbon black, organic dyes, organic pigments, titanium oxide, red lead, and iron oxide can be listed. The content of the colorant can be appropriately selected according to the purpose, etc. The colorant can be used alone or in combination of two or more.

[0222] (Stress Relaxant)

[0223] The molding resin composition of the present embodiment may include a stress relaxant. By including a stress relaxant, the warping deformation of the package and the generation of package cracks can be further reduced. As a stress relaxant, commonly used known stress relaxants (flexible agents) can be cited. Specifically, thermoplastic elastomers such as silicone, styrene, olefin, urethane, polyester, polyether, polyamide, and polybutadiene, indene-styrene-coumarone copolymers, triphenylphosphine oxide, organic phosphorus compounds such as phosphate, natural rubber (natural rubber, NR), acrylonitrile butadiene rubber (acrylonitrile butadiene rubber, NBR), acrylic rubber, urethane rubber, silicone powder and other rubber particles; methyl methacrylate-styrene-butadiene copolymer (methacrylate methyl styrenebutadiene, MBS), methyl methacrylate-silicone copolymer, methyl methacrylate-butyl acrylate copolymer and other rubber particles with core-shell structure. The stress relaxant can be used alone or in combination of two or more.

[0224] Examples of the silicone-based stress relaxant include silicone-based stress relaxants having an epoxy group, silicone-based stress relaxants having an amino group, and silicone-based stress relaxants obtained by polyether-modifying these. Silicone compounds such as silicone compounds having an epoxy group and polyether silicone compounds are more preferred.

[0225] From the viewpoint of dielectric loss tangent, the stress relaxation agent preferably includes at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide.

[0226] When the molding resin composition contains a stress relaxation agent, the amount of the stress relaxation agent is, for example, preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, based on 100 parts by mass of the resin component.

[0227] When the stress relaxation agent contains at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide, the total amount thereof is, for example, preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, based on 100 parts by mass of the resin component.

[0228] The content of the indene-styrene-coumarone copolymer may be, for example, 1 to 20 parts by mass, or 2 to 10 parts by mass, based on 100 parts by mass of the resin component.

[0229] The content of triphenylphosphine oxide may be, for example, 1 to 30 parts by mass, or 5 to 15 parts by mass, based on 100 parts by mass of the resin component.

[0230] The content of silicone stress relaxants, for example, relative to 100 parts by mass of the resin component, may be less than 2 parts by mass, or less than 1 part by mass. The molding resin composition may not include silicone stress relaxants. From the perspective of dielectric loss tangent, in the molding resin composition, it is preferred that the stress relaxant include at least one (preferably both) of indene-styrene-coumarone copolymer and triphenylphosphine oxide, and does not include silicone stress relaxants. The lower limit of the content of silicone stress relaxants is not particularly limited, and may be 0 parts by mass or 0.1 parts by mass.

[0231] From the viewpoint of dielectric loss tangent, the content of the silicone-based stress relaxation agent is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 7% by mass or less, particularly preferably 5% by mass or less, extremely preferably 0.5% by mass or less, and extremely preferably 0.1% by mass or less, relative to the total amount of the molding resin composition. The lower limit of the content of the silicone-based stress relaxation agent is not particularly limited, and may be 0% by mass or 0.1% by mass.

[0232] (Method for preparing molding resin composition)

[0233] The preparation method of the molding resin composition is not particularly limited. As a general method, the following method can be cited: after the components of the prescribed blending amount are fully mixed by a mixer, etc., melt-kneading is performed by a grinding roll, an extruder, etc., and then cooled and crushed. More specifically, for example, the following method can be cited: the prescribed amount of the components is stirred and mixed, and kneaded by a kneader, a roll, an extruder, etc. preheated to 70°C to 140°C, and then cooled and crushed.

[0234] The molding resin composition of the present embodiment is preferably solid at room temperature and pressure (e.g., 25° C., atmospheric pressure). The shape of the molding resin composition when it is solid is not particularly limited, and powder, granular, sheet, etc. can be cited. From the perspective of operability, the size and mass of the molding resin composition when it is in sheet form are preferably the size and mass that match the molding conditions of the package.

[0235] (Characteristics of molding resin composition)

[0236] The relative dielectric constant at 10 GHz of the cured product obtained by compression molding the molding resin composition of the present embodiment under the conditions of a mold temperature of 175° C., a molding pressure of 6.9 MPa, and a curing time of 600 seconds is, for example, 5 to 30. From the viewpoint of miniaturization of electronic parts such as antennas, the relative dielectric constant at 10 GHz of the cured product is preferably 6 to 20, more preferably 7 to 15, and even more preferably 8 to 15.

[0237] The relative dielectric constant is measured at a temperature of 25±3° C. using a dielectric constant measuring device (for example, Agilent Technologies, trade name “Network Analyzer N5227A”).

[0238] The dielectric loss tangent at 10 GHz of the cured product obtained by compression molding the molding resin composition of the present embodiment under the conditions of a mold temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 600 seconds, for example, can be listed as 0.015 or less. From the perspective of reducing transmission loss, the dielectric loss tangent at 10 GHz of the cured product is preferably 0.010 or less, more preferably 0.007 or less, and further preferably 0.005 or less. The lower limit of the dielectric loss tangent at 10 GHz of the cured product is not particularly limited, and for example, 0.001 can be listed.

[0239] The dielectric loss tangent is measured at a temperature of 25±3° C. using a dielectric constant measuring device (for example, Agilent Technologies, trade name “Network Analyzer N5227A”).

[0240] Using the spiral flow measurement mold according to the Epoxy Molding Material Institute (EMMI)-1-66, the flow distance when the molding resin composition is molded under the conditions of a mold temperature of 175°C, a molding pressure of 6.9MPa, and a curing time of 90 seconds is preferably 80cm or more, more preferably 100cm or more, and further preferably 120cm or more. Hereinafter, the flow distance is also referred to as "spiral flow". The upper limit of the spiral flow is not particularly limited, and for example, 200cm can be cited.

[0241] The gel time of the molding resin composition at 175° C. is preferably 30 to 100 seconds, more preferably 40 to 70 seconds.

[0242] The gel time at 175° C. was measured as follows: Specifically, 3 g of a sample of the molding resin composition was measured at 175° C. using a Curelastometer manufactured by JSR Trading Co., Ltd., and the time until the torque curve rose was defined as the gel time (sec).

[0243] (Application of molding resin composition)

[0244] The molding resin composition of the present embodiment is suitable for, for example, electronic component devices described below, and is particularly suitable for production of high-frequency devices. The molding resin composition of the present embodiment can also be used for sealing electronic components in high-frequency devices.

[0245] In particular, in recent years, with the popularization of the fifth-generation mobile communication system (5G), the high-functionality and miniaturization of semiconductor packages (PKG) used for electronic parts devices have continued to develop. Moreover, with the miniaturization and high-functionality of PKG, the development of packaged antennas (Antenna in Package, AiP) as PKGs with antenna functions is also underway. In AiP, in order to cope with the increase in the number of channels accompanying the diversification of information, the radio waves used in communication are made high-frequency, and in the sealing material, it is required to achieve both a high dielectric constant and a low dielectric loss tangent.

[0246] As described above, the molding resin composition in this embodiment can obtain a cured product having both a high dielectric constant and a low dielectric loss tangent. Therefore, in high-frequency devices, it is particularly suitable for packaged antenna (AiP) applications in which an antenna disposed on a supporting member is sealed with the molding resin composition.

[0247] In an electronic component device including an antenna such as a package antenna, when an amplifier for power supply is provided on the side opposite to the antenna, heat is generated due to power supply. From the viewpoint of improving heat dissipation, the molding resin composition used in the manufacture of the electronic component device preferably contains alumina particles as an inorganic filler.

[0248] <Electronic components and devices>

[0249] An electronic component device according to one embodiment of the present disclosure includes a supporting member, an electronic component disposed on the supporting member, and a cured product of the molding resin composition that seals the electronic component.

[0250] Examples of electronic component devices include electronic component devices (e.g., high-frequency devices) in which electronic components (active components such as semiconductor chips, transistors, diodes, thyristors, etc., passive components such as capacitors, resistors, coils, antennas, etc.) are mounted on supporting members such as lead frames, conveyor tapes with completed wiring, wiring boards, glass, silicon wafers, organic substrates, etc., and the electronic component area is sealed with a molding resin composition.

[0251] The type of the supporting member is not particularly limited, and a supporting member generally used in the manufacture of electronic component devices can be used.

[0252] The electronic component may include an antenna, or may include an antenna and an element other than an antenna. The antenna is not limited as long as it functions as an antenna, and may be an antenna element or wiring.

[0253] In addition, in the electronic component device of this embodiment, other electronic components may be arranged on the surface of the support member opposite to the surface on which the electronic components are arranged, as needed. Other electronic components may be sealed by the molding resin composition, may be sealed by other resin compositions, or may not be sealed.

[0254] (Method for manufacturing electronic component device)

[0255] The method for manufacturing an electronic component device according to the present embodiment includes: a step of arranging an electronic component on a supporting member; and a step of sealing the electronic component with the molding resin composition.

[0256] The method for implementing each of the steps is not particularly limited, and can be carried out by a general method. In addition, the types of support members and electronic components used in the manufacture of electronic component devices are not particularly limited, and support members and electronic components commonly used in the manufacture of electronic component devices can be used.

[0257] Examples of methods for sealing electronic components using the molding resin composition include low-pressure transfer molding, injection molding, compression molding, etc. Among these, the low-pressure transfer molding method is generally used.

[0258] [Example]

[0259] Hereinafter, the embodiment will be described in detail by way of examples, but the scope of the embodiment is not limited to these examples.

[0260] <Preparation of molding resin composition>

[0261] The molding resin compositions of Examples and Comparative Examples were prepared by mixing the following components at the blending ratios (parts by mass) shown in Tables 1 to 3. The molding resin compositions are solid at normal temperature and pressure.

[0262] In addition, in Tables 1 to 3, blank columns mean that the components are not contained.

[0263] In addition, the results of determining the total content of calcium titanate particles relative to the inorganic filler used (the "particle ratio (volume %)" in the table), the total content of the inorganic filler relative to the molding resin composition (the "content (volume %)" in the table), and the relative dielectric constant of the entire inorganic filler at 10 GHz (the "filler dielectric constant" in the table) by the above method are also shown in Tables 1 to 3.

[0264] Epoxy resin 1: o-cresol novolac type epoxy resin, epoxy equivalent 200 g / eq ("N500P" manufactured by DIC Corporation)

[0265] Epoxy resin 2: biphenyl aralkyl type epoxy resin, epoxy equivalent 274 g / eq (Nippon Kayaku Co., Ltd., trade name "NC-3000")

[0266] Epoxy resin 3: biphenyl type epoxy resin, epoxy equivalent 192 g / eq (Mitsubishi Chemical Co., Ltd., trade name "YX-4000")

[0267] Hardener 1: Active ester compound, DIC Corporation, trade name "EXB-8"

[0268] Hardener 2: phenol hardener, phenol aralkyl resin, hydroxyl equivalent 170 g / eq (Meiwa Chemical Co., Ltd., trade name "MEH7851 series")

[0269] Inorganic filler 1: Alumina particles, volume average particle size: 5.7 μm, shape: spherical

[0270] Inorganic filler 2: Alumina particles, volume average particle size: 0.7 μm, shape: spherical

[0271] Inorganic filler 3: uncalcined calcium titanate particles, volume average particle size: 8.9 μm, shape: amorphous

[0272] Inorganic filler 4: uncalcined calcium titanate particles, volume average particle size: 0.2 μm, shape: amorphous

[0273] Hardening accelerator: triphenylphosphine / 1,4-benzoquinone adduct

[0274] Coupling agent: N-phenyl-3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., trade name "KBM-573")

[0275] Release agent: montanic acid ester wax (Clariant Japan Co., Ltd., trade name "HW-E")

[0276] Colorant: Carbon black (Mitsubishi Chemical Co., Ltd., trade name "MA600")

[0277] Stress relaxant 1: polyether silicone compound (Momentive Performance Materials, trade name "SIM768E")

[0278] Stress Relaxer 2: Indene-Styrene-Coumarone Copolymer

[0279] Stress Relaxer 3: Triphenylphosphine oxide

[0280] In addition, the volume average particle diameter of each of the inorganic fillers is a value obtained by the following measurement.

[0281] Specifically, first, an inorganic filler is added to a dispersion medium (water) in a range of 0.01 mass % to 0.1 mass %, and the mixture is dispersed for 5 minutes using a bath type ultrasonic cleaning machine.

[0282] 5 ml of the obtained dispersion was poured into a tank, and the particle size distribution was measured at 25° C. using a laser diffraction / scattering particle size distribution measuring apparatus (Horiba, Ltd., LA920).

[0283] The particle diameter of the cumulative value of 50% (volume basis) in the obtained particle size distribution was defined as the volume average particle diameter.

[0284] <Evaluation of molding resin composition>

[0285] (Relative dielectric constant and dielectric loss tangent)

[0286] The molding resin composition is loaded into a vacuum manual press, molded under the conditions of a mold temperature of 175°C, a molding pressure of 6.9MPa, and a curing time of 600 seconds, and cured at 175°C for 6 hours to obtain a plate-shaped cured product (12.5mm vertical, 25mm horizontal, and 0.2mm thick). The plate-shaped cured product is used as a test piece, and a dielectric constant measuring device (Agilent Technologies, trade name "Network Analyzer N5227A") is used to measure the relative dielectric constant and dielectric loss tangent at a temperature of 25±3°C and 10GHz. The results are shown in Tables 1 to 3 ("Relative Dielectric Constant" and "Dielectric Loss Tangent" in the table).

[0287] (Flowability: spiral flow)

[0288] The molding resin composition was molded using a spiral flow measurement mold according to EMMI-1-66 under the conditions of a mold temperature of 180°C, a molding pressure of 6.9 MPa, and a curing time of 120 seconds, and the flow distance (cm) was determined. The results are shown in Tables 1 to 3 ("Flow distance (cm)" in the tables).

[0289] (Thermal conductivity)

[0290] The thermal conductivity of the molding resin composition was evaluated as follows. Specifically, the prepared molding resin composition was used to perform transfer molding under the conditions of a mold temperature of 180°C, a molding pressure of 7 MPa, and a curing time of 300 seconds to obtain a mold-shaped cured product. The specific gravity (density, g / cm 3 The thermal diffusivity (m) of the obtained hardened material was measured by the laser flash method using a thermal diffusivity measuring device (NETZSCH, LFA467). 2 / s). Based on the literature values ​​of the specific heat of each material constituting the sealing resin composition and the blending ratio, the specific heat (J / (g·K)) of the cured product was theoretically calculated. From the above measured values, etc., the thermal conductivity of the cured product was calculated by Formula 2.

[0291] λ=α×Cp×d…(Formula 2)

[0292] Here, λ is the thermal conductivity (W / (m·K)), α is the thermal diffusivity (m 2 / s), Cp is the specific heat (J / (kg·K)), ρ is the density (kg / m 3 ).

[0293] (Gel time)

[0294] 3 g of the molding resin composition was measured at a temperature of 175° C. using a Curelastometer manufactured by JSR Trading Co., Ltd., and the time until the torque curve rises was defined as the gel time (seconds). The results are shown in Tables 1 to 3 (“Gel time (seconds)” in the tables).

[0295] Note that "not possible" in the table means that the gel time was so short that the rise of the torque curve could not be observed.

[0296] [Table 1]

[0297]

[0298] [Table 2]

[0299]

[0300] [Table 3]

[0301]

[0302] As shown in Tables 1 to 3, the molding resin compositions of Examples tend to provide cured products having a low dielectric loss tangent while maintaining relative dielectric constants, as compared with the molding resin compositions of Comparative Examples.

[0303] The entire text of the disclosure of PCT / JP2022 / 016913 filed on March 31, 2022 is incorporated into this specification by reference.

[0304] All documents, patent applications, and technical specifications described in this specification are incorporated herein by reference to the same extent as if each document, patent application, or technical specification was specifically and individually described as being incorporated by reference.

Claims

1. A molding resin composition comprising: hardening resin; and The inorganic filler comprises at least one of silica particles and alumina particles and calcium titanate particles. The content of the calcium titanate particles is 10 volume % or more and less than 30 volume % relative to the total amount of the inorganic filler. The total content of the inorganic filler exceeds 60% by volume based on the total amount of the molding resin composition. 2 . The molding resin composition according to claim 1 , wherein the curable resin comprises an epoxy resin, and the molding resin composition further comprises a curing agent. 3 . The molding resin composition according to claim 2 , wherein the curing agent comprises an active ester compound. The molding resin composition according to claim 3 , wherein the hardener further comprises a phenol hardener. 5 . The molding resin composition according to claim 2 , wherein the epoxy resin comprises at least any one of an o-cresol novolac-type epoxy resin, a biphenyl aralkyl-type epoxy resin, and a biphenyl-type epoxy resin. 6 . The molding resin composition according to claim 1 , wherein the inorganic filler comprises alumina particles. 7 . The molding resin composition according to claim 1 , further comprising a stress relaxant. 8 . The molding resin composition according to claim 7 , wherein the stress relaxation agent comprises at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide. 9 . The molding resin composition according to claim 1 , wherein the content of the silicone-based stress relaxer is 5% by mass or less based on the total amount of the molding resin composition. 10 . The molding resin composition according to claim 8 , which does not contain a silicone-based stress relaxant. 11 . The molding resin composition according to claim 1 , which contains no titanium compound particles other than calcium titanate particles. 12 . The molding resin composition according to claim 1 , which is used for a high-frequency device. 13 . The molding resin composition according to claim 12 , which is used for sealing electronic parts in high-frequency devices. 14 . The molding resin composition according to claim 1 , which is used for encapsulating an antenna.

15. An electronic component device, include: Supporting members; Electronic components are arranged on the supporting member; as well as A cured product of the molding resin composition according to any one of claims 1 to 14, which seals the electronic component.

16. The electronic part device according to claim 15, wherein the electronic part includes an antenna.

Citation Information

Cited By

  • Resin composition and use thereof

    WO2026137337A1